2023
DOI: 10.1002/smll.202207066
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Targeted Delivery of Bifunctional Circular Aptamer‐ASO Chimera to Suppress the SARS‐CoV‐2 Proliferation and Inflammation

Abstract: Inhibition of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection and excessive in ammation is the current task in the prevention and treatment of COVID-19. Here, we designed a dualfunction circular aptamerASO chimera (circSApt-NASO) to suppress SARS-CoV-2 replication and in ammation. The chemically unmodi ed circSApt-NASO exhibited high serum stability by arti cial cyclization, signi cantly enhancing the utility of oligonucleotides. It presents great e ciency in knocking down, demonstrating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…275 Yang et al designed a circular aptamer-ASO chimera for the simultaneous suppression of SARS-CoV-2 replication and inflammation. 276 On the one hand, the aptamers bound to the S protein contributed to driving the aptamer-ASO chimera to be efficiently internalized by ACE-overexpressing host cells. On the other hand, the ASO targeting N genes potently expressed anti-N-induced inflammatory activity after entering cells and achieved the inhibition of SARS-CoV-2 proliferation.…”
Section: Applications Of Aptamer-based Assemblies In Sars-cov-2 Detec...mentioning
confidence: 99%
“…275 Yang et al designed a circular aptamer-ASO chimera for the simultaneous suppression of SARS-CoV-2 replication and inflammation. 276 On the one hand, the aptamers bound to the S protein contributed to driving the aptamer-ASO chimera to be efficiently internalized by ACE-overexpressing host cells. On the other hand, the ASO targeting N genes potently expressed anti-N-induced inflammatory activity after entering cells and achieved the inhibition of SARS-CoV-2 proliferation.…”
Section: Applications Of Aptamer-based Assemblies In Sars-cov-2 Detec...mentioning
confidence: 99%
“…(d) Design of dual‐function circSApt1‐NASO2 and mechanism of inhibiting inflammatory and replication of SARS‐CoV‐2. Reproduced with permission [77] . Copyright 2023, Wiley.…”
Section: Sars‐cov‐2 Aptamer‐based Diagnosis and Treatmentmentioning
confidence: 99%
“…Thus, targeting the N gene and inhibiting its expression is another effective therapeutic strategy. Based on this, the Zhao group constructed a dual‐function circular SApt1‐NASO2 chimera (circSApt1‐NASO2) using ST‐6‐1 (SApt1) and antisense oligonucleotides (NASO2) to silence N genes [77] (Figure 8d). CircSApt1‐NASO2 showed high serum stability, and not only blocks the S‐TLR4 interaction by SApt1 component to inhibit S protein‐introduced inflammation, but also specifically silences the N gene and blocks the replication of the virus by the NASO2 component to inhibit N protein‐induced inflammation even if SARS‐CoV‐2 has entered the host cells.…”
Section: Sars‐cov‐2 Aptamer‐based Diagnosis and Treatmentmentioning
confidence: 99%
“…The chimera inhibited both S-induced inflammation and viral N gene-dependent replication, displaying efficacy against the original strain and omicron variant, which highlights the potential of aptamers as synergistic treatments. 50 Further studies revealed that aptamer-functionalized lipid nanoparticles encapsulating siRNAs could target the nucleocapsid phosphoprotein. Molecular docking and antiviral tests indicated a significant inhibition of infection in human lung cells.…”
Section: Aptamer Conjugation With Advanced Technology: New Insight In...mentioning
confidence: 99%